Pediatric burden and seasonality of human metapneumovirus over 5 years in Managua, Nicaragua. Issue 6 (14th August 2022) - Hacker, Kathryn; Kuan, Guillermina; Vydiswaran, Nivea; Chowell‐Puente, Gerardo; Patel, Mayuri; Sanchez, Nery; Lopez, Roger; Ojeda, Sergio; Lopez, Brenda; Mousa, Jarrod; Maier, Hannah E.; Balmaseda, Angel; et al.
Abstract: Background: Human metapneumovirus (hMPV) is an important cause of pediatric respiratory infection. We leveraged the Nicaraguan Pediatric Influenza Cohort Study (NPICS) to assess the burden and seasonality of symptomatic hMPV infection in children. Methods: NPICS is an ongoing prospective study of children in Managua, Nicaragua. We assessed children for hMPV infection via real‐time reverse‐transcription polymerase chain reaction (RT‐PCR). We used classical additive decomposition analysis to assess the temporal trends, and generalized growth models (GGMs) were used to estimate effective reproduction numbers. Results: From 2011 to 2016, there were 564 hMPV symptomatic infections, yielding an incidence rate of 5.74 cases per 100 person‐years (95% CI 5.3, 6.2). Children experienced 3509 acute lower respiratory infections (ALRIs), of which 160 (4.6%) were associated with hMPV infection. Children under the age of one had 55% of all symptomatic hMPV infections (62/112) develop into hMPV‐associated ALRIs and were five times as likely as children over one to have an hMPV‐associated ALRI (rate ratio 5.5 95% CI 4.1, 7.4 p < 0.001). Additionally, symptomatic reinfection with hMPV was common. In total, 87 (15%) of all observed symptomatic infections were detected reinfections. The seasonality of symptomatic hMPV outbreaks varied considerably. From 2011 to 2016, four epidemic periods were observed, following a biennial seasonal pattern. The mean ascending phase of the epidemic periods were 7.7 weeks, with an overall mean estimated reproductive number of 1.2 (95% CI 1.1, 1.4). Conclusions: Symptomatic hMPV infection was associated with substantial burden among children in the first year of life. Timing and frequency of symptomatic hMPV incidence followed biennial patterns.